2017
DOI: 10.3389/fphys.2017.00199
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Medication Response Prediction for Attention-Deficit Hyperactivity Disorder: Learning in the Model Space vs. Learning in the Data Space

Abstract: Attention-Deficit Hyperactive Disorder (ADHD) is one of the most common mental health disorders amongst school-aged children with an estimated prevalence of 5% in the global population (American Psychiatric Association, 2013). Stimulants, particularly methylphenidate (MPH), are the first-line option in the treatment of ADHD (Reeves and Schweitzer, 2004; Dopheide and Pliszka, 2009) and are prescribed to an increasing number of children and adolescents in the US and the UK every year (Safer et al., 1996; McCarth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
0
12
0
1
Order By: Relevance
“…Personality measures are easily administered in the clinical setting, and our finding indicates that personality might be relevant to predict treatment response. Researchers trying to predict treatment responders vs. non-responders in ADHD based on machine learning could, therefore, potentially benefit from including a personality questionnaire among their measures [54]. Whether personality measures will also predict different responses to different types of treatments could further be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Personality measures are easily administered in the clinical setting, and our finding indicates that personality might be relevant to predict treatment response. Researchers trying to predict treatment responders vs. non-responders in ADHD based on machine learning could, therefore, potentially benefit from including a personality questionnaire among their measures [54]. Whether personality measures will also predict different responses to different types of treatments could further be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of assessing stimulant‐naïve ADHD patients on an individual basis gives us the opportunity of capturing information about the pathophysiology underlying the symptoms of ADHD without the bias of treatment‐induced brain alterations. Because all previous ML‐based MRI studies of adults never treated for ADHD symptoms were carried out using child and adolescent samples , the findings reported herein represent the first neurobiological evidence supporting the individual diagnosis of stimulant‐naïve ADHD patients specifically in adulthood. The diagnostic performance achieved in our study is similar to that reported in recent, large‐scale ML‐based MRI studies investigating potentially severe psychiatric disorders in adults such as schizophrenia and better than figures reported in studies of other major mental conditions such as bipolar disorder .…”
Section: Discussionmentioning
confidence: 82%
“…The literature presents variable and partly conflicting results concerning the use of clinical data to predict response to MPH. Age, weight, gender, comorbid anxiety or oppositional defiant disorder, IQ, academic achievement, disease duration, severity of symptoms, level of maternal ADHD symptoms, and prior atomoxetine use have all been shown to have some predictive effect (Buitelaar et al, 2011; Buitelaar, Van Der Gaag, Swaab-barnkvhld, & Kuipkr, 1995; Chazan et al, 2011; Fredriksen, Dahl, Martinsen, Klungsoyr, Haavik, et al, 2014; Ishii-Takahashi et al, 2015; Johnston et al, 2015; Setyawan et al, 2015; Treuer et al, 2014; Wong et al, 2017). It has been difficult to predict treatment response to stimulants using neuropsychological tests in ADHD patient as well, and results from these studies have also been conflicting (Coghill et al, 2007; Wong et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have examined response to medication in ADHD patients, to see whether baseline measures can be used to predict treatment response, primarily using clinical variables and neuroimaging markers (Buitelaar et al, 2011; Coghill, Rhodes, & Matthews, 2007; Ishii-Takahashi et al, 2015; Johnston et al, 2015; Kim, Sharma, & Ryan, 2015). In such studies, different statistical methods and machine learning approaches have been employed (Ishii-Takahashi et al, 2015; Wong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%